Combining Vascular Targeting Agents with Radiation: An Effective Anti-Tumor Treatment but Associated with Radiation-Induced Systemic Toxicity - Miwako Nomura; Rumi Murata; Line Brøndum; Eva Ehrnrooth; Brita S. Sørensen; Michael R. Horsman (Radiation)
This study investigated the effect of combining radiation with an angiogenesis inhibitor and vascular disrupting agent on tumor response and systemic toxicity. CDF1 mice with 200 mm3 foot implanted C3H mammary carcinomas were treated with TNP-470 (100 mg/kg every second day for 2 weeks; s.c.) and combretastatin A-4 phosphate (CA4P; 1 × 250 mg/kg, i.p.). Radiation (230-kV X-rays) was locally administered to tumors of restrained non-anesthetized mice. Response was tumor growth delay and change in mouse body weight. Radiation induced changes in serum levels of 10 cytokines up to 72-h after irradiation were measured using a Luminex assay. The results showed that TNP-470 (100 mg/kg × 7) or CA4P (250 mg/kg × 1) significantly (Student’s t-test; p < 0.05) inhibited tumor growth; the greatest effect when these two drugs were combined. TNP-470 and CA4P, alone or together, also significantly enhanced tumor response to radiation. No systemic toxicity occurred with drugs administered alone or in combination, but toxicity was observed when TNP-470 was combined with radiation. Serum cytokine levels only showed a significant transient increase in IL-6 1-h after irradiating. In conclusion, combining different acting vascular targeting agents with radiation increased anti-tumor activity. However, this benefit may sometimes be associated with a radiation-induced inflammatory response increasing systemic toxicity.